The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1055/s-0041-1730018
|View full text |Cite
|
Sign up to set email alerts
|

Rhinological Status of Patients with Nasolacrimal Duct Obstruction

Abstract: Introduction Studying the state of the nasal cavity and its sinuses and the morphometric parameters of the inferior nasal conchae, as well as a comparative analysis of obtained values in patients with primary (PANDO) and secondary acquired nasolacrimal duct obstruction (SALDO), is relevant. Objective To study the rhinological status of patients with PANDO) and SALDO). Methods The present study was based on the results of computed tomography (CT) dacryocystography in patients with PANDO (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
0
0
Order By: Relevance
“…Some studies also mention that people with nasal septal deviation are prone to rhinitis, and the basic lesions of chronic dacryocystitis may be caused by simple rhinitis and hypertrophy rhinitis. Therefore, it can be preliminarily concluded that the occurrence of this disease is related to nasal septum deviation [40][41][42]. Many patients with lacrimal passage obstruction are complicated by nasal septal deviation.…”
Section: Analysis Of Nasal Septum Deviation In Patients With Chronic ...mentioning
confidence: 99%
“…Some studies also mention that people with nasal septal deviation are prone to rhinitis, and the basic lesions of chronic dacryocystitis may be caused by simple rhinitis and hypertrophy rhinitis. Therefore, it can be preliminarily concluded that the occurrence of this disease is related to nasal septum deviation [40][41][42]. Many patients with lacrimal passage obstruction are complicated by nasal septal deviation.…”
Section: Analysis Of Nasal Septum Deviation In Patients With Chronic ...mentioning
confidence: 99%